Dendritic Cell-Based Approaches for Therapeutic Immune Regulation in Solid-Organ Transplantation - Giuseppe Vassalli (Journal of Transplantation)
To avoid immune rejection, allograft recipients require drug-based immunosuppression, which has significant toxicity. An emerging approach is adoptive transfer of immunoregulatory cells. While mature dendritic cells (DCs) present donor antigen to the immune system, triggering rejection, regulatory DCs interact with regulatory T cells to promote immune tolerance. Intravenous injection of immature DCs of either donor or host origin at the time of transplantation have prolonged allograft survival in solid-organ transplant models. DCs can be treated with pharmacological agents before injection, which may attenuate their maturation in vivo. Recent data suggest that injected immunosuppressive DCs may inhibit allograft rejection, not by themselves, but through conventional DCs of the host. Genetically engineered DCs have also been tested. Two clinical trials in type-1 diabetes and rheumatoid arthritis have been carried out, and other trials, including one trial in kidney transplantation, are in progress or are imminent.